OP35 Management of Chronic Hepatitis B; streamlining a patient pathway. (20th September 2022) - Roskilly, Anna; Hameed, Saad; Thomson, Sam
Abstract : Background: Hepatitis B is a global public health problem and treatment aims to suppress viral load, in turn reducing transmission, fibrosis progression and the risk of hepatocellular carcinoma (HCC). Nucleos(t)ide Analogue (NA) therapy including Entecavir and Tenofovir are first line. Indications for treatment are Hepatitis B viral load > 2, 000 IU/ml alongside ALT > ULN and/or at least moderate histological necroinflammation or fibrosis. Those with cirrhosis should be given anti-viral therapy. Surveillance for HCC is recommended in patients with cirrhosis, those on treatment or with a family history of HCC. Methods: Medical record review of patients with documented HbSAg positive tests were undertaken. Demographic data and viral load were recorded. Fibrosis stage (Fibroscan and Histological) were tabulated. Treatment with anti- viral therapy was recorded. The reviewing Hepatologist assessed if patients met treatment criteria on the basis of EASL clinical guidelines. Hepatitis B E antigen positivity and Hepatitis Delta testing were also recorded. Results: 121 patients (73 male, 44 female) were identified. Mean age was 46.2 years (Range 28–78). 12.4% had cirrhosis on the basis of biopsy or Fibroscan. 74% (91 patients) had a baseline Fibroscan. The majority had F0/F1 fibrosis (77%). 22 patients underwent liver biopsy. Variation in reporting of histological features was noted. 64 patients had a baseline HBV DNA >2000 IU/ml. 30 patients had HBV DNA > 20, 000 at baseline and 24 of these received treatment with NA therapy. 44 patients received treatment overall. 27 received Entecavir (61%), 15 (34%) received Tenofovir, 1 patient received both. 51 patients met EASL criteria for treatment, 29 of these were on treatment at the time of data collection. Hepatitis Delta was tested in 56 patients, all were negative. Hepatitis E Antigen was tested in 112 patients, 20 patients displayed positivity. 61 patients (50%) had ultrasound HCC surveillance. Conclusions: There is an unmet need for dedicated Hepatitis B clinics and a streamlined pathway for treatment in our hospitals. Many patients can be managed in a virtual or nurse led combined Fibroscan clinic. We now have a database of patients with chronic Hepatitis B to ensure follow up and treatment according to clinical practice guidelines. HCC surveillance with ultrasound was undertaken in all patients with cirrhosis, however this was not done routinely in patients receiving anti-viral therapy. We have produced a treatment, monitoring and surveillance guideline. Cost effectiveness was also considered and following review, prescribing was transferred to in hospital pharmacy only.